Analisis Gaya Bahasa dalam Lirik Lagu “Semua Aku dirayakan” Karya Nadin Amizah Kajian Stilstika - Nadia Maulina; Dwi Wahyu Candra Dewi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The aim of this research is to study and analyze the language styles contained in the lyrics of Nadin Amizah's song "All I'm Celebrated" using stylistic studies. Song lyrics are a type of literature that aims to be expressive and beautiful and contain deep emotional messages. In the lyrics, figures of speech such as personification, metaphor, repetition, symbolism and hyperbole are analyzed using qualitative descriptive methods. The research results show that this language style functions to strengthen meaning, create a reflective atmosphere, and create emotional closeness between the singer and the listener. The lyrics of this song show a poetic message about self-acceptance and the unique beauty of language through the stylistic approach used. According to this research, "All of Me is Celebrated" is an example of a musical that is stylistically and can be analyzed like a literary work.